2020
DOI: 10.1002/bdr2.1743
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal alcohol exposure induced congenital heart diseases: From bench to bedside

Abstract: Alcohol consumption is increasing worldwide. Many child-bearing-aged women consume alcohol during pregnancy, intentionally or unintentionally, thereby increasing the potential risk for severe congenital diseases. Congenital heart disease (CHD) is the most common birth defect worldwide and can result from both hereditary and acquired factors. Prenatal alcohol exposure (PAE) is considered a key factor that leads to teratogenesis in CHD and its specific phenotypes, especially defects of the cardiac septa, cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 101 publications
1
13
0
1
Order By: Relevance
“…Experimental models with high-dose embryo exposure to ethanol have recapitulated this wide array of presentation [ 102 ]: the embryological impact seems to be mediated by both alteration in retinoic acid signaling, and profound disturbance of histone regulation with hyper-H3K9 acetylation through activation of histone-acetyl-transferases [ 103 ]. Ethanol exposure also appears to target CNN derivatives specifically, explaining the increased prevalence of conotruncal pathologies [ 104 ]. Current efforts in protective supplementation, similar to folic acid in the case of valproic acid toxicity, have shown potential reversal of alcohol exposure with glutathione (the “master antioxidant”) administration, but hopes of preventing the cardiac phenotype would imply prenatal continuous administration [ 102 ].…”
Section: Environmental Slightsmentioning
confidence: 99%
“…Experimental models with high-dose embryo exposure to ethanol have recapitulated this wide array of presentation [ 102 ]: the embryological impact seems to be mediated by both alteration in retinoic acid signaling, and profound disturbance of histone regulation with hyper-H3K9 acetylation through activation of histone-acetyl-transferases [ 103 ]. Ethanol exposure also appears to target CNN derivatives specifically, explaining the increased prevalence of conotruncal pathologies [ 104 ]. Current efforts in protective supplementation, similar to folic acid in the case of valproic acid toxicity, have shown potential reversal of alcohol exposure with glutathione (the “master antioxidant”) administration, but hopes of preventing the cardiac phenotype would imply prenatal continuous administration [ 102 ].…”
Section: Environmental Slightsmentioning
confidence: 99%
“…Moreover, while these cranial NCCs give rise to numerous important cell populations that contribute to facial morphology and cranial nerve development, the potential lifelong impact on health is because cranial NCCs give rise to cardiac NCCs, a subset of which become thymic mesenchymal cells [164]. These are cell populations from which FASD-associated diseases such as congenital heart disease and impaired immune function originate [146,[165][166][167].…”
Section: +mentioning
confidence: 99%
“…One toxicant effect of in utero exposure to ethanol is congenital heart disease (CHD). PAE results in an increased risk of the development of specific types of CHDs, such as conotruncal defects and transposition of the great arteries [165,166]. These types of CHDs are linked to cardiac NCC apoptosis and abnormal epigenetic modifications [168], both of which may result from the toxic and teratogenic consequences of PAE, respectively.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…A few prior reports have suggested that alcohol use during pregnancy is associated with increased CHD. 9 , 10 , 11 , 12 , 13 Up to 30% of patients diagnosed with fetal alcohol spectrum disorder may harbor a CHD. 9 However, little information is available on which component of cardiac development may be most vulnerable to the teratogenic effects of alcohol.…”
mentioning
confidence: 99%